« Mobile » de Michel Butor : entre le scriptural et le pictural - Dahmany, Khalid (Wydawnictwo Naukowe UAM, 2007)
Generically, M. Butor's Mobile is an unclassifiable product because of its deliberately confusing form. This is a text whose aesthetics is not very common and whose value is emphasized by the scriptural deviations it hides. From the abundance of the typographic blanks (and their "geometrisation") to the mixture of the characters, passing through the syntactic sabotage, everything is expressed in a dynamics of break-up and incompletion. The whole resembles, in its homogenous heterogeneity, a collage or rather these blankets - the "quilts" - made by craftsmen of different pieces of cloth sewn together and frequently referred to by Butor in this Study for a representation of the United States.
Michel Butor's Mobile: between the scriptural and the pictural
Keywords: Butor Michel; Mobile